Hypoxia-inducible factor-1α contributes to hypoxia-induced chemoresistance in gastric cancer - Liu, Lili; Ning, Xiaoxuan; Sun, Li; Zhang, Hongbo; Shi, Yongquan; Guo, Changcun; Han, Shuang; Liu, Jie; Sun, Shiren; Han, Zheyi; Wu, Kaichun; Fan, Daiming (Cancer science, 2008)
Hypoxia induced drug resistance is a major obstacle in the development of effective cancer therapy. Our previous study revealed that hypoxia‐inducible factor‐1 (HIF‐1), the major transcriptional factor significantly activated by hypoxia, was overexpressed in gastric vincristine‐resistant cells SGC7901/vincristine (VCR) under normoxic conditions, which suggested that it was associated with drug resistance in gastric cancer cells. In the present study, a colony‐forming assay revealed that hypoxia and forced HIF‐1α expression increased maximal –8.9‐fold or –14.8‐fold of IC50 toward vincristine in gastric cancer cell lines SGC7901 and SGC7901/VCR, respectively (P < 0.01). Annexin‐V/propidium iodide staining analysis revealed hypoxia or forced HIF‐1α expression reduced apoptosis by 24% or 18% in SGC7901 cells (P < 0.05). Flow cytometry analysis of intracellular adriamycin revealed that hypoxia and forced expression of HIF‐1α increased –1.79‐fold or –2.36‐fold of the adriamycin releasing index, respectively (P < 0.05). However, resistance acquisition subject to hypoxia in vitro and in vivo was suppressed by blocking HIF‐1α expression with siRNA. We further demonstrated that HIF‐1 α overexpression showed a 1.85‐fold increased expression of Bcl‐2 and a 2.16‐fold decreased expression of Bax, and also showed significantly induced expression of p‐gp and MRP1, which indicated that HIF‐1α may confer hypoxia‐induced drug resistance via inhibition of drug‐induced apoptosis and decreases in intracellular drug accumulation. (Cancer Sci 2008; 99: 121–128)